Interpretive Structural Modeling and House of Risk Implementation for Risk Association Analysis and Determination of Risk Mitigation Strategy - Christine Natalia; Yulitari Flora Theresa Br. Hutapea; Chendrasari Wahyu Oktavia; Trifenaus Prabu Hidayat (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2020)
The increasingly fierce industry competition causes each company needs strong supply chain activities as part of the company to be able to survive in an environment full of competition. In carrying out supply chain activities, it is certainly inseparable from supply chain risks that can disrupt supply chain activities. In supply chain risk it is important to know the key risks as the risks that trigger the other risks in the supply chain. This study aims to identify the relationship of risk and mitigation to reduce the causes of the risk. The interpretive structural modeling (ISM) approach is applied to solve problems related to risk linkages and produced key risks which are the risks that most influence the occurance of other risks. The key risks obtained are then processed using the house of risk (HOR) approach to determine the priority of risk mitigation actions. ISM result obtained four key risks, namely the risk element of inputting data error when entering the number of goods and spesifications, product spesification errors desired by the customer, frequent changes in customer design requests and revisions to the design drawings. Then the result of the HOR method obtained four recommended priority mitigation actions, namely updating information on a scheduled basis, conducting briefings every day before work, coordinating and reconfirming requests for product spesifications, and implementing more strigent worker selection procedures. The linkage of the causes of risk, the validation of the ISM model statistically and the weighting of the triggered criteria are several aspects that further research is needed.